Optimising Financial Transparency in the Oregon Cluster through the Development of a Web-Based System and Intelligent AI Chatbot - Tyoffadhil Haidar; Permata Sari, Dian (P3M Politeknik Negeri Bengkalis, 2026)
Managing finances within neighborhood associations frequently encounters persistent hurdles regarding transparency and the speed of information delivery. This study develops a web-based financial platform for the Oregon Cluster, uniquely integrated with a Gemini-powered virtual assistant to enable real-time data inquiries. The novelty of this research lies in the integrated service model that pairs an automated payment gateway with conversational AI, effectively removing traditional bottlenecks in community reporting. Performance evaluation showed significant improvements compared to manual processes payment verification latency dropped by over 99.9% (from 24–48 hours to less than 10 seconds), and the time required for residents to access specific balance information was reduced by approximately 95% (from 5–10 minutes to near-instantaneous retrieval). Functional validation via Black Box Testing achieved a 100% success rate across 15 core modules. Furthermore, a System Usability Scale (SUS) evaluation with 21 respondents yielded an average score of 85.36, placing the system in the